Development Of V Cryo-Plate Method Of Ludisia Discolor (Ker Gawl.) A. Rich For Long-Term Germplasm Conservation - Rajan, Kirutika Selva (2022)
Ludisia discolor is a jewel orchid that is well known for the striking leaves than its flowers. Other than being used as an ornamental plant, this orchid is also being exploited for its medicinal properties. Hence, L. discolor facing possible depletion in its natural habitat lately due to over-harvesting. Recently, the latest cryopreservation methods such as V cryo-plate is needed for long-term germplasm conservation. This study aims to develop a V cryo-plate cryopreservation method for L. discolor axillary buds to perform microscopy analysis of cryopreserved explants, determine the water content changes, and genetic stability between control and treated explants. Six (6) parameters have been optimized in this V cryo-plate method which are preculture concentration and duration, types of loading solution, duration on PVS2, thawing temperature, and thawing duration.